Analysis of the Assessment of the Introduction of Hibiscus Syriacus L. Based on Phenological Observations - I. Z., Zakriddinov; F. J, Sharofiddinova; D. D., Bekmirzayeva (American Journal of Biology and Natural Sciences, 2025)
This article presents data on the introduction evaluation of Hibiscus Syriacus L. imported from other regions to the Namangan region and changes in the first-year adaptation process of planted bushes for control purposes. Data on the growth of 1-year-old shoots, lignification status, and initial cold temperature resistance indicators are presented until December 1.